2022
DOI: 10.1055/s-0042-1756304
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Heparin Resistance and Its Viscoelastic Assessment in Critically Ill COVID-19 Patients

Abstract: Critically ill COVID-19 patients present an inflammatory and procoagulant status with a high rate of relevant macro- and microvascular thrombosis. Furthermore, high rates of heparin resistance have been described; yet, individualized anticoagulation by drug monitoring has not been sufficiently researched. We analyzed data from critically ill COVID-19 patients treated at Innsbruck Medical University Hospital with routinely adapted low-molecular-weight heparin (LMWH) doses according to anti-Xa peak levels, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Bösch J et al found that elevated C-reactive protein values can play a role in resistance to LMWH activity, which could explain why patients from our study with lower values were more exposed to overdose. 8 Although levels above the target range can potentially pose a greater risk of complications, only 6% had levels ≥0.70 IU/mL, and the rate of major bleeding was 4%, not particularly higher compared to that described in the medical literature (2%–6%). 6 , 7 , 9 …”
mentioning
confidence: 75%
“…Bösch J et al found that elevated C-reactive protein values can play a role in resistance to LMWH activity, which could explain why patients from our study with lower values were more exposed to overdose. 8 Although levels above the target range can potentially pose a greater risk of complications, only 6% had levels ≥0.70 IU/mL, and the rate of major bleeding was 4%, not particularly higher compared to that described in the medical literature (2%–6%). 6 , 7 , 9 …”
mentioning
confidence: 75%